Adolescent Vulnerabilities and Opportunities: Developmental and Constructivist Perspectives - Amsel, Eric; Smetana, Judith G. (Interdisciplinary perspectives on knowledge and development : the Jean Piaget symposium series, 2011)
This book explores the central importance of adolescents' own activities in their development. This focus harkens back to Jean Piaget's genetic epistemology and provides a theoretically coherent vision of what makes adolescence a distinctive period of development, with unique opportunities and vulnerabilities. An interdisciplinary and international group of contributors explore how adolescents integrate neurological, cognitive, personal, interpersonal and social systems aspects of development into more organized systems.